Students Perceptions on Project-Based Learning Implementation In At English Education Department - Yulianti, Nia; Roza, Veni (Yayasan Lembaga Studi Makwa, 2023)
Project based learning is a student-centered teaching method that organizes around project task. According to this theory, project-based learning is believed to have a various advantages and benefits to students learning experience. However, in its implementation, researcher found some issues regarding to learner experience using this learning method. Some of them are students’ lack of creativity that leads them to do the plagiarism and students’ lack of independency that results them to not be responsible on their own project task. Therefore research referring to these phenomenom need to be conducted. This study is purposed to identify students’ learning perception through project based learning. The research also investigated the impact of project-based learning implementation towards students learning experience. Quantitative research applied in this research. The data was collected through questionnaire. Sample of the research were students at 6 semester at English for Jurnalism of English Education Department at IAIN Bukittinggi, with total respondents are 32. The result of the study showed that most of the students assume that project-based learning has positive impact towards their learning experience. This can be seen from the data that researcher gathered from the field. First step of PBL implementation, choosing a project topic, 54,46% of students have a positive assumption with the criteria neutral. Second, project focus and development resulted 58,87% score with the criteria neutral. And the last step is project docummentation with the score 61,87% indicates positive. Data showed these three steps of PBL implementation, for the most responses of the respodents, have a positive impact in for their learning experience. However, some constructive advices need to be applied while implementing this learning method in order to make it more effective. Abstrak Pembelajaran berbasis proyek adalah metode pengajaran yang berpusat pada siswa yang mengatur seputar tugas proyek. Menurut teori tersebut, pembelajaran berbasis proyek diyakini memiliki berbagai kelebihan dan manfaat bagi pengalaman belajar siswa. Namun dalam implementasinya, peneliti menemukan beberapa hal yang berkaitan dengan pengalaman peserta didik dalam menggunakan metode pembelajaran ini. Beberapa di antaranya adalah kurangnya kreativitas siswa yang menyebabkan mereka melakukan penjiplakan dan kurangnya kemandirian siswa yang mengakibatkan mereka tidak bertanggung jawab atas tugas proyeknya sendiri. Oleh karena itu perlu dilakukan penelitian yang mengacu pada fenomena tersebut. Penelitian ini bertujuan untuk mengidentifikasi persepsi belajar siswa melalui pembelajaran berbasis proyek. Penelitian ini juga menginvestigasi dampak implementasi pembelajaran berbasis proyek terhadap pengalaman belajar siswa. Penelitian kuantitatif diterapkan dalam penelitian ini. Pengumpulan data dilakukan melalui kuesioner. Sampel dalam penelitian ini adalah 32 mahasiswa semester 6 mapel Inggris Jurnalisme Jurusan Pendidikan Bahasa Inggris. Hasil penelitian menunjukkan bahwa sebagian besar siswa beranggapan bahwa pembelajaran berbasis proyek berdampak positif terhadap pengalaman belajar mereka. Hal ini terlihat dari data yang peneliti kumpulkan dari lapangan. Pelaksanaan PBL tahap pertama, pemilihan topik proyek, 54,46% siswa berasumsi positif dengan kriteria netral. Kedua, fokus dan pengembangan proyek menghasilkan skor 58,87% dengan kriteria netral. Dan tahap terakhir adalah dokumentasi proyek dengan skor 61,87% menunjukkan positif. Data menunjukkan ketiga langkah penerapan PBL ini, sebagian besar tanggapan responden, berdampak positif bagi pengalaman belajar mereka. Namun, beberapa saran konstruktif perlu diterapkan saat menerapkan metode pembelajaran ini agar lebih efektif.